DYNAMICS OF TRAFFIC VIOLATIONS FROM THE PERSPECTIVE OF CULTURAL CRIMINOLOGY: A STUDI IN PEKANBARU, INDONESIA - Kasmanto Rinaldi; Satrio Abdillah (Kanun Jurnal Ilmu Hukum, 2023)
This article examines the dynamics of traffic violations in Pekanbaru, where community has been accustomed to it. The research method used is legal normative and legal-empirical, where  data was obtained through surveys involving respondents from the community on  how far understanding of traffic violations is percieved. Research findings indicate that frequent traffic violations have various consequences, such as an increase in incidents. Data obtained from the Pekanbaru Police Department over the last 4 years shows an increase in accident cases that stem from frequent traffic violations have become a common behavior in Pekanbaru communities, where people often perceive them as ordinary and even as part of everyday life. This is supported by survey results showing that 46% of respondents stated that the main reason for their traffic violations is because they are accustomed to doing so. In cultural criminology, the behavior of traffic offenders is considered a form of traffic crime culture. This is due to the high frequency and patterns of criminal activities that occur every day, even at all times, making it a deviant culture and an accepted habit in society. This would need to legal culture interventions to raise legal awareness on traffic law and the risks of violation to it.